Harmonious Values of Kupatan Tradition on Plosokandang Society, Tulungagung - Khabibur Rohman; Moh. Irsyad Fahmi Malik Rahma; Nailul Wirdah (Karsa: Journal of Social and Islamic Culture, 2021)
This article aims to draw a comprehensive overview of some values which exist in Kupatan tradition on Plosokandang society, Tulungagung. The current research implements descriptive analysis, meanwhile the data collection method are interview, observation, and documentation. Kupatan is one tradition which happens by the reason of as a celebration that occurs after Eid al-Fitr. On Plosokandang-Tulungagung, Kupatan is held on the seventh day of Shawwal or 7 days after Eid. The result of the study shows that there is a value of harmony among society while applying kupatan. During kupatan, the people of Plosokandang distributed some kupat and various traditional foods to everyone who came to visit at this event who they didn't even know before. Moreover, the value of social harmony contained in the activity of Kupatan not only in according to Islam, but is also needed for a multicultural country like Indonesia.